2011
DOI: 10.3109/14992027.2010.540582
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of pure-tone hearing threshold levels among adolescents and adults in the United States by gender, ethnicity, and age: Results from the US National Health and Nutrition Examination Survey

Abstract: Cumulative distributions of audiometric pure-tone thresholds for a non-occupationally noise-exposed population vary with demographic characteristics (e.g. gender, ethnicity, age), tested ear, and stimulus frequency. However, commonly-used audiometric databases either do not take these differences into account, or account for them using data not easily generalized to the US population. The objective of this study was to obtain distributions that are generalizable to the US population without significant history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
2
19
0
1
Order By: Relevance
“…Several studies describing hearing in normal subjects (without noise exposure) have described better hearing thresholds in black versus white subjects (Dreisbach, et al, 2007;Henselman, et al, 1995;Flamme, et al, 2011). As early as 1931 better hearing thresholds have been described in black noise-exposed subjects compared to white counterparts (Bunch & Raiford, 1931).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies describing hearing in normal subjects (without noise exposure) have described better hearing thresholds in black versus white subjects (Dreisbach, et al, 2007;Henselman, et al, 1995;Flamme, et al, 2011). As early as 1931 better hearing thresholds have been described in black noise-exposed subjects compared to white counterparts (Bunch & Raiford, 1931).…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that white persons are more susceptible to noise than are African American persons. [9][10][11]44 Analysis of these factors in future research on predictors of recreational NIHL would be of interest.…”
Section: Limitationsmentioning
confidence: 99%
“…[9][10][11][12] This association is partly biased by the cumulative noise exposure inherent to an increasing age. Second, several studies on occupational NIHL 9,10,[12][13][14] have shown that men are more likely to develop NIHL than are women. For the same amount of occupational noise, Kovalova et al 13 observed significantly more NIHL in men than in women.…”
mentioning
confidence: 99%
“…Furthermore, cross-sectional trends in hearing sensitivity differ with race/ethnicity (Driscoll and Royster 1984;Flamme, Deiters, and Needham 2011;Royster et al 1980). Lempert and Henderson (1973) did not report the race/ethnicity of the screened sample used to derive the NIOSH age adjustment tables, and there were too few participants in that study to produce stable estimates for race/ethnicity subgroups.…”
Section: Introductionmentioning
confidence: 99%